2022
DOI: 10.1007/s11657-022-01064-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of English-language videos available on YouTube as a source of information on osteoporosis

Abstract: Osteoporosis awareness is essential for preventing osteoporotic fractures. Social media platforms have enormous potential to both support and deter patients' decisions on healthcare. The current study demonstrated that the majority of YouTube videos on osteoporosis provide useful information with sufficient quality. Purpose YouTube is the most popular video-sharing platform for patients seeking online information about their medical condition. However, there are concerns regarding the accuracy and quality of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
3
14
0
1
Order By: Relevance
“…However, these findings are consistent with previous studies which have found comparably low DISCERN scores when evaluating content on YouTube about other otolaryngologic topics such as cholesteatoma, 26 hypoglossal nerve stimulation, 27 trigeminal neuralgia, 28 and functional endoscopic sinus surgery 29 . Low quality and reliability of content on YouTube has been reported in other specialties as well, 30,31 although videos about osteoporosis and keratoconus have been found to be of higher quality 32,33 . Thus, while it is certainly possible for health‐related videos to be of high quality, video topics meeting this requirement are the exception, not the norm.…”
Section: Discussionsupporting
confidence: 89%
“…However, these findings are consistent with previous studies which have found comparably low DISCERN scores when evaluating content on YouTube about other otolaryngologic topics such as cholesteatoma, 26 hypoglossal nerve stimulation, 27 trigeminal neuralgia, 28 and functional endoscopic sinus surgery 29 . Low quality and reliability of content on YouTube has been reported in other specialties as well, 30,31 although videos about osteoporosis and keratoconus have been found to be of higher quality 32,33 . Thus, while it is certainly possible for health‐related videos to be of high quality, video topics meeting this requirement are the exception, not the norm.…”
Section: Discussionsupporting
confidence: 89%
“…25,27,28 While good quality content is possible, it is not the standard for treatment-related videos on YouTube. 15,29 This study supports this phenomenon, as GD treatment videos demonstrated poor reliability, quality, and overall value according to the DISCERN instrument. These data are consistent with previous studies displaying low DISCERN scores for YouTube content on thyroid-related topics, such as thyroid cancer and hypothyroidism.…”
Section: Discussionsupporting
confidence: 63%
“…The complex nature of BPI leads patients to often seek answers and consolation on social on YouTube should look toward providing content with peerreviewed sources (Osman et al, 2022). On the same note, videos in which there was a physician presenting the information had greater reliability and quality of information, lending credence to the idea that misleading information will generally come from for-profit healthrelated institutions and not primary providers, as noted in other studies (Onder et al, 2022) Unfortunately, however, views were being allocated to less reliable sources, as evidenced by results of the linear regression, leading to potential misinformation among patients. Ku et.…”
Section: Discussionmentioning
confidence: 79%